Identification of beta-lactamase genes and molecular genotyping of multidrug-resistant clinical isolates of Klebsiella pneumoniae - Azadeh Ferdosi-Shahandashti; Abazar Pournajaf; Elaheh Ferdosi-Shahandashti; Fatemeh Zaboli; Kasra Javadi (BMC Microbiology)
Abstract Background Klebsiella pneumoniae is a clinically relevant pathogen that has raised considerable public health concerns. This study aims to determine the presence of beta-lactamase genes and perform molecular genotyping of multidrug-resistant (MDR) K. pneumoniae clinical isolates. Methods Clinical isolates of MDR K. pneumoniae were collected from educational hospitals affiliated with Babol University of Medical Sciences. The isolates of K. pneumoniae were identified through standard microbial and biochemical tests. Antibiotic resistance was assessed using disk diffusion, modified Hodge test (MHT), combined disk, and polymerase chain reaction (PCR) methods. Enterobacterial Repetitive Intergenic Consensus (ERIC)-PCR was performed for molecular typing. Results A total of 42 MDR K. pneumoniae isolates were obtained from various clinical specimens. The highest antibiotic resistance was observed for ampicillin (100%), while the lowest resistance was noted for amikacin (19.04%). The MHT indicated that 38.09% of K. pneumoniae isolates produced carbapenemase enzymes. Metallo-beta-lactamase (MBL) production was found in 54.76% of isolates. Molecular detection of beta-lactamase genes revealed the presence of bla NDM (21.42%), bla KPC (42.85%), bla TEM (76.19%), bla SHV (47.16%), and bla CTX−M (80.95%) genes. ERIC-PCR molecular typing identified seven distinct genetic patterns among the isolates. Conclusions This investigation demonstrates the high resistance levels of K. pneumoniae strains. The beta-lactamase genes with the highest and lowest frequencies correspond to bla CTX−M and bla NDM genes, respectively. ERIC-PCR dendrograms suggest a common origin for K. pneumoniae clinical isolates and the propagation of similar clones within hospital wards. These findings indicate that K. pneumoniae isolates are highly virulent, necessitating the development of more effective resistance-fighting techniques and gene transfer research. Clinical trial number Not applicable.